Development of Remote Laboratory for Distance Learning Practicum Online And Real-Time Digital Electronics Subjects - Hendra Jaya; Lumu Lumu; Sapto Haryoko; Sutarsi Suhaeb (Universitas Negeri Makassar, 2020)
This study aims to: 1) find out how to Develop Remote Laboratory as a new tool for online and realtime practicum learning in digital electronics; 2) find out how to use Remote Lab that meets the valid, practical and effective criteria. This research is a type of research and development (R&D) where the product can work effectively and be ready to use. The development of hardware and software in the form of Remote Lab media is carried out with an engineering approach where the stages are: analysis, design, implementation, and evaluation. The analysis used in this study is a descriptive analysis that describes the results of development, validator responses and trial results. Analysis of software and hardware is done by considering the minimum specifications, with reference to the development of software for the media that is effective and practical. The use of Remote Lab can be applied at the Vocational School by looking at the results of the development based on the validation of the material experts (Content Aspect of 4.45% with very good category, and the Design Practicum aspect obtained a score of 4.4 with a very good category), validation of media experts (Aspect of Visual Display obtained score 4.47 in the excellent category, real-time aspects obtained a score of 4.5 in the excellent category, programming aspects obtained a score of 4.57 in the excellent category), Analysis of the Effectiveness and Practicality of Using Remote Labs obtained a score of 4.56 with the category very effective, then Practical Assessment of Remote Lab products obtained a score of 4.9 with a very practical category. The creation of online and realtime distance learning practicum systems that can facilitate students who are constrained by distance and inadequate school facilities. Practical equipment so that learning outcomes in practicums can be met according to their competencies.